A qualitative study of adolescent perceptions of electronic cigarettes and their marketing: Implications for prevention and policy. Issue 4 (2nd October 2017) - Johnson, Andrea C.; Mays, Darren; Hawkins, Kirsten B.; Denzel, Molly; Tercyak, Kenneth P.
ABSTRACT: This study examined youths' perceptions of electronic cigarettes ("e-cigarettes"), sources of e-cigarette exposure, and preferred sources of e-cigarette health information. Participants ( n = 25, M age 15.0 years) recruited during primary care visits completed an in-depth qualitative interview assessing these topics. Most participants (72%) perceived e-cigarettes as "healthier" than cigarettes and reported e-cigarette advertising exposure (80%) and interpersonal exposure (60%). Participants reported that advertisements portray e-cigarettes as less harmful than cigarettes and novel products. Most (72%) indicated their doctor was their preferred source of e-cigarette health information, suggesting pediatric health care providers are well-positioned to counsel patients to prevent e-cigarette use.